Utilization Of Artificial Intelligence In Digital Learning: 21st Century Learning Innovation In The Era Of Society 5.0 - Sri Sunarti (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This study investigates the utilization of Artificial Intelligence (AI) in digital learning as a key innovation for advancing 21st-century education within the context of Society 5.0. Using a descriptive-exploratory mixed-methods approach, the research integrates both qualitative and quantitative data: a comprehensive literature review and a survey of 183 educators, including teachers, supervisors, and madrasah principals. Findings reveal that although awareness of AI tools (such as ChatGPT, Grammarly, and adaptive learning platforms) is moderate, consistent application in classrooms remains limited, with only 27.2% of educators frequently using such technologies. Major challenges identified include insufficient infrastructure, limited professional development, and a lack of confidence in integrating AI tools effectively. Despite these barriers, most educators acknowledge AI's potential to enhance learning effectiveness, personalize instruction, and streamline administrative tasks. The study concludes that successful AI integration requires targeted strategies, including sustained teacher training, equitable access to digital infrastructure, clear ethical guidelines, and institutional support. Rather than replacing educators, AI should be positioned as a complementary tool that enhances pedagogical practices and strengthens human-centered learning. These findings contribute to the broader discourse on digital transformation in education, offering practical insights for policymakers, school leaders, and educators aiming to leverage AI-driven innovations to equip students with critical 21st-century competencies.